THE IMPACT OF HIGH COMMISSION RATES ON LOCAL TOURISM ENTREPRENEURS- A STUDY FOCUSED ON ONLINE TRAVEL AGENCIES IN KERALA - N S, Surya; P T, Muhammedismail (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Online Travel Agencies (OTAs) have transformed the tourism industry by offering global reach and streamlined booking processes. However, high commission rates imposed by OTAs have raised concerns among local tourism entrepreneurs in Kerala. This study explores the economic and operational impacts of these commission structures on small and medium-sized tourism enterprises (SMEs), including homestays, adventure tour operators, and boutique hotels. Through qualitative and quantitative analysis, the research examines financial strain, pricing strategies, and dependency on OTAs. The findings reveal that while OTAs provide visibility and customer inflow, high commissions reduce profit margins, limit reinvestment in quality services, and increase reliance on alternative direct booking strategies. The study suggests policy interventions and strategic adaptations to balance the benefits of OTA partnerships with sustainable business growth for local entrepreneurs.